Association Between ALK Immunohistochemistry and MYCN Gene Amplification in Pediatric Neuroblastoma - Lertsatit, Anchaleerat; Wiwatwarayos, Kulachet; Chamninawakul, Padol (Journal of Health Science of Thailand, 2025)
MYCN amplification is a critical prognostic marker in neuroblastoma requiring molecular diagnostics often unavailable in resource-limited settings. This retrospective study evaluated ALK immunohistochemistry as a potential surrogate marker for MYCN amplification in 49 primary neuroblastomas from patients aged £18 years. ALK immunohistochemistry (clone D5F3) was scored as high (³50% tumor cells) or low (<50%) by two independent pathologists blinded to MYCN status determined by FISH using standard criteria (ratio ³4.0 or >10 copies/nucleus). MYCN amplification was present in 35% (17/49) of cases, while ALK-high expression occurred in 73% (36/49). ALK-high expression significantly associated with MYCN amplification (p=0.02; OR=9.6, 95%CI = 1.13–81.9), with 94% (16/17) of MYCN-amplified tumors showing ALK-high expression versus 63% (20/32) of non-amplified tumors. Diagnostic performance showed high sensitivity (94%) and negative predictive value (92%), but limited specificity (38%) and positive predictive value (44%). While ALK immunohistochemistry cannot replace molecular MYCN testing, its high sensitivity and NPV support its use as a preliminary screening tool in diagnostic algorithms, particularly in resource- limited settings, helping prioritize cases for molecular testing while identifying candidates for ALK-targeted therapy.